Heterologous expression of the helicoverpa armigera stunt virus in Saccharomyces cerevisiae - Venter, Philip Arno (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2002)
Lepidopteran insects like Helicoverpa armigera, more commonly known as the cotton bollworm, are economically important pests of a wide variety of crops throughout the world. The Helicoverpa armigera stunt virus (HaSV), a tetravirus with a bipartite single-stranded positive-sense RNA genome, has great potential as a biological pesticide against H. armigera. The larger genomic strand of this virus (RNA1) encodes the viral replicase, while the other (RNA2) encodes the 71 kDa capsid protein precursor (p71). 240 copies of p71 assemble into a procapsid with the concomitant encapsidation of the viral RNA. This is followed by a complex maturation event that is characterized by the autoproteolytic cleavage of p71 into the 64 kDa capsid protein (P64) and a 7 kDa peptide (p7). The rearrangements that occur during maturation results in the formation of mature HaSV capsids that can thereupon deliver RNA to other susceptible host cells. The principal objective of the research described in this study was to demonstrate that this virus could be assembled in Saccharomyces cerevisiae. S. cerevisiae expression vectors were constructed for the production of p71. This protein was detected in cell lysates from two different strains of S. cerevisiae, both containing either chromosomal or episomal copies of an expression cassette for P71. A number of factors relating to the expression of P71 (e.g. strains used, expression loci and expression rate) and the preparation of protein extracts from S. cerevisiae (e.g. the presence of various protease inhibitors and salt concentrations) were examined to attain optimal levels of soluble p71. A small fraction of the optimized soluble p71 was shown to be in the form of virus-like particles (VLPs), with a yield of â‰¤10â · VLPs from a 1.5l culture of P71â º cells. These particles were exclusively in the procapsid form, had a similar buoyant density to that of wild-type HaSV and could undergo maturation when the pH was reduced to 5. S. cerevisiae vectors were constructed for the episomal expression of the HaSV genomic RNAs. These vectors directed the transcription of RNA1 and RNA2 transcripts, which had similar sizes to those of the HaSV genomic RNAs. Mature HaSV particles were purified from cells, transgenic for P71, RNA1 and RNA2, by way of two different virus purification protocols that were developed during this study. RT-PCR analyses on RNA-extracts from these particles demonstrated that RNA transcripts, which were produced in trans with p71, could be encapsidated by HaSV capsids in S. cerevisiae. A droplet-feed bioassay on H. armigera larvae demonstrated that the S. cerevisiae-derived HaSV particles caused impaired larval development. This response was correlated with the detection of HaSV RNA2 in RNA extractions from larvae that were used in this bioassay. The results that were generated through the course of this study, provided proof for the concept of the non-host production of infectious HaSV particles from S. cerevisiae. This work could serve as a foundation for future research on the development of an expression system for the large-scale production of this virus as a biopesticide.
Keywords: Helicoverpa armigera; Saccharomyces cerevisiae